Composition of Anthocyanins in Colored Grains and the Relationship of Their Non-Acylated and Acylated Derivatives - Sladjana Zilic; Dejan Dodig; Jelena Vancetovic; Nikola Grcic; Vesna Peric; Primoz Titan; Vuk Maksimovic (Polish Journal of Food and Nutrition Sciences)
Colored grains are rich sources of anthocyanins that could play an important role in the prevention of various diseases associated with oxidative stress. Bearing in mind that cereals are widely grown crops, anthocyanins-rich colored grains could be used as a functional food ingredient that provide health benefits to a large part of human world's population. This study investigated composition and content of anthocyanins in the grain of blue popping maize, deep purple maize, purple wheat and black soybean. The relationship of acylated and non-acylated forms before and after alkaline hydrolysis of anthocyanin extracts has been also studied. Deep purple maize had the highest content of total anthocyanins as much as 4988.90 mg CGE/kg d.m. Ten anthocyanins were identified in blue popping maize, of which two are isomers of cyanidin-3-(malonylglucoside) and three of cyanidin-3-(dimalonyl-β-glucoside). In the deep purple maize, purple wheat and black soybean seven, nine and three anthocyanins have been identified, respectively. Cyanidin derivatives were predominant and their acylated forms accounted about 98, 29, 71 and 0% of the total anthocyanins content in the grains, respectively. According to the study, acylated derivatives were completely degraded under effect of highly alkaline pH. However, in the beginning of their degradation they were transformed to its non-acylated parents. The results could be useful to better understanding of the nature of anthocyanin in colored grains and, in that regard, their use for the derivation of food products with functional potential, as well as of natural dyes and pharmaceutical ingredients.